New Media Disruption Towards Mainstream Media Resistance (Study of Fajar and Tribun Timur Daily in Makassar City) - Erniwati; Unde, Andi Alimuddin; Cangara, Hafied; Hidayatullah, Fauzan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
The phenomenon of disruption penetrates all lines of life. Technological advances influence almost all human activities and activities. Conventional media loyal to their old style will slowly lose their fans. The methodology used in this study is qualitative-descriptive, with a case study approach consisting of several cases in Fajar & Tribun Timur Makassar using a purposive sampling technique. This study's results indicate decreased newspaper readers, but print media advertising growth is still growing. Some factors affected were the decline in circulation turnover triggered by a decline in public interest in reading Beria through print media. The strategy is digitizing newspapers through e-papers, content innovation, networking, and organizational restructuring. The disruption of new media by the Fajar & Tribun Timur newspaper industry managers process opportunities and threats. Opportunities in question are 1) the Strength of human resources in providing accurate information to the public. 2) Establish collaboration with stakeholders. 3) The company's management's Strength in response to journalistic style changes. 4) Technology Development. While the threats faced are 1) The presence of new media. 2) The speed of new media in providing information compared to the mainstream media. 3) High costs and 4) Business competitors. The electronic world is full of creations and cyber-journalistic abilities that can be combined in synergy with print media. This step can only be done if the leadership of this new media is controlled by a team that has technological, management, and cyber journalistic skills that are highly competitive in information competition.